1998
DOI: 10.1007/s005350050100
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β isoforms in alcoholic liver disease

Abstract: The increased deposition of extracellular matrix proteins in the liver is a key factor in the morbidity and mortality of alcoholic liver disease (ALD). This increased fibrosis may be due to a superabundance of profibrogenic factors such as transforming growth factor-beta (TGF-beta). The original peptide is now called TGF-beta 1, and two other isoforms have been recognized in humans (TGF-beta 2 and TGF-beta 3). It was the aim of the present study to determine the expression of the TGF-beta isoforms in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
(28 reference statements)
2
16
0
1
Order By: Relevance
“…These results indicated that the expression of TGF -beta 1 was highes in more active and advanced ALD patients. Santos et al [31] also demonstrated similar results in liver specimens. The presence of TGF-beta1 expression could be recognized as a risk factor for active and advanced alcoholic liver disease.…”
Section: Discussionsupporting
confidence: 72%
“…These results indicated that the expression of TGF -beta 1 was highes in more active and advanced ALD patients. Santos et al [31] also demonstrated similar results in liver specimens. The presence of TGF-beta1 expression could be recognized as a risk factor for active and advanced alcoholic liver disease.…”
Section: Discussionsupporting
confidence: 72%
“…20 Increased levels of TGF-1 and its other isoforms have been shown to occur in animal models of hepatic fibrosis 21,22 and in patients with alcoholic liver disease. 23 Transgenic mice that overproduce the active form of TGF-developed significant fibrotic lesions in the liver and kidneys. 24 Recently, another line of transgenic mice that overexpress TGF-1 under the control of the C-reactive protein (CRP) promoter was developed.…”
Section: Activation Of Hscmentioning
confidence: 99%
“…An early event in the development of liver fibrosis is the activation of hepatic stellate cells (HSCs), the major cell type responsible for increased synthesis of extracellular matrix proteins (5). An elevated level of transforming growth factor ␤1 (TGF-␤1) is also observed in the damaged liver, and it has a close correlation with fibrogenic changes in HSCs and liver tissue (6)(7)(8). In addition, decreased matrix metalloproteinase 9 (MMP-9) expression was observed in alcoholic liver fibrosis (9).…”
mentioning
confidence: 99%